Enhanced dual-effect of adsorption and photodegradation of SiO2 embedded TiO2 hybrid catalyst for improved decolourization of methylene blue - Sonar, Shilpa K.; Wagh, Reshma V.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Awate, Shobhana V. (Water Air and Soil Pollution, 2013)
Dual-effects of adsorption and photodegradation over titania, silica embedded titania, silica and commercial Degussa P-25 samples were studied for the decolourization of methylene blue in aqueous medium. Silica embedded titania and silica were prepared using inexpensive polymeric version of ethyl silicate as a source of silica. Catalysts were characterized by X-ray diffraction, scanning electron microscopy, UV-Vis spectroscopy and low temperature (77 K) nitrogen adsorption measurements. Among all the catalysts, silica embedded titania has exhibited faster decolourization of methylene blue solution on account of the enhancement of adsorption followed by degradation. An amount of the catalyst and the initial dye concentration of MB solution were found to influence the decolourization activity. Compared to titania catalyst, silica embedded titania and Degussa P-25 have shown the red shift in their UV-Vis spectrum. The experimental data of the reaction fitted well to the pseudo first order kinetic model. In present studies, the adsorption mechanism for the decolourization of MB solution was found to be applicable for an intra particle diffusion model.
Keywords: Adsorption; kinetic model; Methylene blue; Photodegradation; Silica embedded titania